Reading and alexia - Starrfelt, R; Woodhead, Z (Elsevier, 2021)
Alexia refers to an impairment in reading caused by injury to the brain in patients who could read normally before their brain injury. Alexia is most commonly observed following stroke, but may arise as a consequence of other brain disorders too. The reading impairment will have a different presentation depending on which parts of the brain are affected. Central alexias are reading impairments that are related to more widespread language problems, while peripheral alexia refers to reading impairment caused by perceptual or attentional deficits. The study of acquired reading disorders has been central in the development of cognitive models of the reading system. We present the main cognitive models of reading, and the central cognitive and clinical aspects of the main forms of alexia.